Control of scabies fluctuation during COVID-19 pandemic - Abdullah; Saeed Ahmad; Wedad Albalawi; Nadir Omer (Alexandria Engineering Journal)
This study investigates the dynamics of scabies infestation using a mathematical model, analyzing its stability, sensitivity, and optimal control. We analyze the model for stability, and the results demonstrate the system’s stable behavior under specific conditions, suggesting the possibility of effective control. The model is subjected to sensitivity analysis, revealing the most influential parameters affecting the infestation’s dynamics. These parameters are identified as key targets for intervention. The optimal control strategy is derived using Pontryagin’s Maximum Principle, minimizing the cost of intervention while effectively controlling the infestation. The results demonstrate the importance of early intervention and sustained control efforts. This study provides a comprehensive understanding of scabies infestation dynamics, highlighting the critical factors influencing its spread and the most effective control strategies. The findings inform public health policy and guide resource allocation to combat scabies infestations effectively. The major contributions include improved understanding of scabies transmission dynamics, identification of critical parameters, development of evidence-based control strategies, evaluation of resource allocation effectiveness, and assessing intervention impact. It may also contribute to public health policy, resource allocation, disease surveillance, and intervention strategies. Numerical simulations are carried out to support our analytical findings.